Existence of ω-periodic solutions for a delayed chemostat with periodic inputs. (October 2020) - Amster, Pablo; Robledo, Gonzalo; Sepúlveda, Daniel
Abstract: This paper proposes an ω -periodic version of the Ellermeyer model of delayed chemostat. We obtain a sufficient condition ensuring the existence of a positive ω -periodic solution. Our proof is based on the application of the generalized continuation theorem. In addition, as a consequence of the implicit function theorem, we obtain a uniqueness result for sufficiently small delays.